2008
DOI: 10.1161/hypertensionaha.108.110932
|View full text |Cite
|
Sign up to set email alerts
|

Renin Inhibition by Aliskiren Prevents Atherosclerosis Progression

Abstract: Abstract-Hypertension is associated with increased risk of cardiovascular diseases. Antihypertensive treatment, particularly blockade of the renin-angiotensin system, contributes to prevent atherosclerosis-mediated cardiovascular events. Direct comparison of different antihypertensive treatments on atherosclerosis and particularly plaque stabilization is sparse. ApoE Ϫ/Ϫ mice with vulnerable (2-kidney, 1-clip renovascular hypertension model) or stable (1-kidney, 1-clip renovascular hypertension model) atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
118
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 22 publications
10
118
0
5
Order By: Relevance
“…There was significant macrophage expression within atheroma from mice with chronic RAS (Figure 5A), consistent with previous studies showing that chronic RAS is associated with a vascular inflammatory reaction 10, 11, 16. Macrophages were detectable within atheroma from mice in the D4LR and D8LR groups, but at levels significantly less than observed in atheroma from mice in the chronic RAS group (Figure 5B).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…There was significant macrophage expression within atheroma from mice with chronic RAS (Figure 5A), consistent with previous studies showing that chronic RAS is associated with a vascular inflammatory reaction 10, 11, 16. Macrophages were detectable within atheroma from mice in the D4LR and D8LR groups, but at levels significantly less than observed in atheroma from mice in the chronic RAS group (Figure 5B).…”
Section: Resultssupporting
confidence: 91%
“…Abdominal aortic atheroma were present in mice in the D4LR, D8LR, and chronic RAS groups, whereas there were no atheroma in the 16 mice that underwent sham surgery. There was significant accumulation of macrophages within atheroma in the chronic RAS group, consistent with past studies that showed pronounced inflammatory response in the aorta 4 weeks10, 11 and 90 days16 after unilateral renal artery clipping in ApoE −/− mice. Restoration of renal blood flow either 4 or 8 days after unilateral partial RAS was associated with lower levels of macrophage infiltration than chronic RAS, strongly suggesting that restoration of renal blood flow has an anti‐inflammatory effect.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, aliskiren attenuated the intense pro-inflammatory profile in retina of Ren-2 rats with diabetes or OIR, with a reduction in leucostasis, ICAM-1 production and ED-1 immunolabelling to control levels. There is evidence that aliskiren reduced the macrophage content of atherosclerotic plaques [30], leucocyte adhesion in femoral arteries [31] and the number of CD11b + and CD11c + antigen presenting cells in a model of multiple sclerosis [32]. The results of the present study are consistent with these findings, and highlight the potent anti-inflammatory properties of aliskiren.…”
Section: Discussionsupporting
confidence: 89%